IOT Network Automation Implementation in Router Configuration Handling: Implementasi IOT Network Automation Pada Penanganan Konfigurasi Router - A F Limas Ptr; B H Hayadi (Cered Indonesia Institute, 2022)
Network Automation or network automation in terms is the process of automating the configuration, management, testing, deployment, and operation of physical and virtual devices in a network. Thus, in this study, we will discuss the design of an IoT-based system for handling router configurations. This IoT-based router handling system uses the Python programming language which will be used as a command source on the server as a router configuration control. This system can also remotely use a smartphone so that it can be seen whether the configuration is running or system error. With this IoT-based router handling system, it will be easier for engineers to remotely and configure routers and save time in the router configuration process.